2005
DOI: 10.1590/s1807-59322005000100010
|View full text |Cite
|
Sign up to set email alerts
|

SERUM Β2-Microglobulin VALUES AMONG HEALTHY BRAZILIANS USING a DPC IMMULITE® ASSAY

Abstract: PURPOSE: The present study was designed to determine the normal range of serum beta 2-microglobulin (Sb 2 M) levels among healthy volunteers in Brazil. Levels of Sb 2 M are elevated in human immunodeficiency virus (HIV)-infected patients and have been shown to be the best predictor of HIV infection status and of some malignant disorders, especially multiple myeloma. In order to achieve its optimal use in Brazilian clinical diagnosis, an adequate reference interval study was performed for Sb 2 M IMMULITE ® assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…For instance, one study has reported that healthy adults with an average age of 40 to 86 years old exhibit elevated serum B2M levels with progressive aging. Similar findings have been reported in other studies (20)(21)(22)(23). Additionally, B2M in the older Chinese population can reportedly affect both the frailty phenotype and index.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, one study has reported that healthy adults with an average age of 40 to 86 years old exhibit elevated serum B2M levels with progressive aging. Similar findings have been reported in other studies (20)(21)(22)(23). Additionally, B2M in the older Chinese population can reportedly affect both the frailty phenotype and index.…”
Section: Discussionsupporting
confidence: 91%
“…The 97th percentile of β 2 M in the examined population ranged between 1.54 and 2.84 mg/L. There is very few research that determines the correlation of age, gender or ethnicity with the concentration of β 2 M in healthy subjects (15,16). In 2005, Fillipin proved a significant difference of concentration of β 2 M in healthy subjects in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its well-documented role in pathological conditions, data on normal b2m expression are surprisingly scarce, represented by only a handful of papers (16)(17)(18)(19)(20)(21)(22). These reports show remarkable variations in the methods used, age and number of reference individuals and statistical analyses of the data.…”
mentioning
confidence: 99%